101k views
4 votes
Determine g(x + a) - g(x) for the following function.g(x) = 3x^2 - 5x

User JRJurman
by
6.0k points

1 Answer

2 votes

Answer:

3a² + 6ax + 5a

Step-by-step explanation:

Given the following function

g(x) = 3x² - 5x

Determine g(x+a)

g(x+a) = 3(x+a)² - 5(x+a)

Expand the result

g(x+a) = 3(x² + 2ax + a²) - (5x - 5a)

g(x+a) = 3x² + 6ax + 3a² - 5x + 5a

Determine g(x + a) - g(x)

g(x + a) - g(x) = 3x² + 6ax + 3a² - 5x + 5a - (3x² - 5x)

g(x + a) - g(x) = 3x² + 6ax + 3a² - 5x + 5a - 3x² + 5x

Collect the like terms

g(x + a) - g(x) = 3x² - 3x² - 5x + 5x + 6ax + 3a² + + 5a

g(x + a) - g(x) = 6ax + 3a² + 5a

g(x + a) - g(x) = 3a² + 6ax + 5a

Hence the required result for the function g(x + a) - g(x) is 3a² + 6ax + 5a

User Steve Buzonas
by
5.8k points